2022
DOI: 10.37829/hf-2022-p11
|View full text |Cite
|
Sign up to set email alerts
|

Public perceptions of health and social care: what government should know

Abstract: Public perceptions of health and social care 4Public satisfaction with the health service has fallen to a 20-year low. 6 By the end of 2021, the 'grace period' of widespread support for the NHS and its staff during the pandemic 7,8 had been replaced by a more pessimistic outlook. 9 Public satisfaction fell across all NHS services -from emergency care in hospitals to general practice and dentistry. 6 Satisfaction with social care is even lower. 6 Early in the pandemic, high numbers of deaths in care homes and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…This finding contrasts with general public views on the NHS, with a 2021 survey showing that over half of respondents (57%) found that the general standard of care provided by the NHS had worsened during the preceding years. 15 Interpretation of our findings has to be set in the context of the wider pandemic: at the time of data collection in summer 2021, the UK had emerged from exceptionally high levels of hospitalisations linked to COVID-19; yet, the vaccine roll-out was generally perceived as a UK success story. 16 Overall, our findings highlight the need for the UK and devolved governments to value the importance of public trust in the health system and take appropriate measures to avoid undermining such trust.…”
Section: Discussionmentioning
confidence: 96%
“…This finding contrasts with general public views on the NHS, with a 2021 survey showing that over half of respondents (57%) found that the general standard of care provided by the NHS had worsened during the preceding years. 15 Interpretation of our findings has to be set in the context of the wider pandemic: at the time of data collection in summer 2021, the UK had emerged from exceptionally high levels of hospitalisations linked to COVID-19; yet, the vaccine roll-out was generally perceived as a UK success story. 16 Overall, our findings highlight the need for the UK and devolved governments to value the importance of public trust in the health system and take appropriate measures to avoid undermining such trust.…”
Section: Discussionmentioning
confidence: 96%
“…4 Patients are also concerned about the pressure on GPs and point to lack of staff and limited funding as the main reasons why. 5 The public is clear that government has the greatest responsibility for addressing these problems. 67 Policymakers should listen.…”
Section: Discussionmentioning
confidence: 99%
“…Public and patient satisfaction with general practice have hit record lows, 3,4 people are finding it harder to get GP appointments 4 and concerns about GP access are high on the public agenda. 5 Job satisfaction among GPs has fallen too 6 and many are considering leaving the profession. 6,7 Policymakers are taking notice.…”
Section: Introductionmentioning
confidence: 99%
“…Overcoming language barriers yields many benefits for clinicians, patients and the healthcare system, which is especially important at a time of low public satisfaction with the healthcare system. 20 The Office for Health Improvement and Disparities indicates that working with professional interpreters ensures accuracy and impartiality, which in turn minimise the legal risk of misinterpretation of important clinical information and safeguarding risks. 19 Thus, for example, interpreter-mediated consultations could contribute to identifying and supporting women experiencing gender-based violence.…”
Section: The Impact Of Overcoming Language Barriersmentioning
confidence: 99%